Modeling correlation between radial distribution of pores volume and temperature in high burn-up UO2 pellet - Suwardi . (Jurnal Teknologi Bahan Nuklir, 2014)
Abstract Temperature distribution has been evaluated by using different model of pore distribution. Pellet pore and its distribution change with burnup, especially in radial direction. Typical high burnup data of radial distribution of power density and porosity have been chosen in this study. Different pore distribution models have been studied for related temperature, in correlation with high burn up thermal properties. Both pore and temperature distributions have strong influence on thermal conductivity, then on temperature distribution. Finite element method has been developed for resolving the implicit temperature distribution from the governing non-linear system differential equations of heat transfer. The effect of number of elements on calculated temperature has been studied, and it shows exponential relation, which effect reduce to under 1 % when the number of radial elements  > 25. Above the number, there is no significant different result. At high burnup, the pore is very high at rim zone and nearly homogenous at other radial position while the temperature distribution is nearly parabolic with radial position with peak at pellet center. The antagonist effect has been calculated as combined correction factor, which shows a maxima and minima value at radial position ~ 0.8 and ~ 0.9 respectively. The pore distribution at high burnup decreases the thermal conductivity ~ 10 % of outer radial zone of pellet. Because the outer surface of pellet temperature is fixed, the different pore models resulted in different of peak temperature at the center of pellet. Comparison of the temperature modeling distribution and the measured one permit the determination of best choice of pore model.   Keywords: UO2 pellet, high burnup, pore, temperature, distribution.   Abstrak Distribusi temperatur telah dievaluasi dengan menggunakan model yang berbeda dari distribusi pori. Pori pelet dan distribusi dengan derajat bakar berubah terutama dalam arah radial. Data derajat bakar tinggi khas distribusi radial dari kerapatan daya dan porositas telah dipilih dalam penelitian ini. Model distribusi pori yang berbeda telah dipelajari untuk suhu terkait dalam korelasinya dengan sifat termal pada derajat bakar tinggi. Kedua distribusi memiliki pengaruh yang kuat pada konduktivitas termal, selanjutnya pada distribusi temperatur. Metode elemen hingga telah dikembangkan untuk menyelesaikan distribusi temperatur implisit dari sistem persamaan diferensial non-linear dari perpindahan panas. Pengaruh jumlah elemen pada suhu dihitung telah dipelajari, dan itu menunjukkan hubungan eksponensial, efek itu menurun. hingga <1% bila jumlah elemen radial> 25. Di atas jumlah itu tidak menghasilkan beda signifikan. Pada derajat bakar tinggi  pori-pori sangat tinggi di zona luar dan hampir homogen pada posisi radial lainnya, sedangkan distribusi temperatur hampir parabola dengan posisi radial dengan puncak pada pusat pelet. Efek antagonis telah dihitung sebagai gabungan faktor koreksi, yang menunjukkan maxima dan minima nilai pada posisi radial ~0,8 dan ~0,9 . Distribusi pori pada derajat bakar tinggi menurunkan konduktivitas termal dari 10% radial luar pelet. Karena permukaan luar suhu pelet adalah tetap, model pori yang berbeda menghasilkan beda suhu puncak di pusat pelet. Model yang baik dapat dipilih dengan pembandingan distribusi temperature dari berbagai model faktor koreksi pori dengan data eksperimen.   Kata kunci: UO2 pelet, derajat bakar tinggi, pori, suhu, distribusi.